Penerapan Metode Belajar Tuntas Dalam Proses Pembelajaran - Andi Hamrina Bakri (IAIN PAREPARE, 2020)
This paper describes the method of complete learning in the teaching and learning process as a form of solving the problem of low learning achievement of students associated with low absorption or not yet realized learning process skills that emphasize the active role of students focused on the problem of mastery learning